Marketing research of development of food retail networks in Ukraine - Мірошник, Марія Володимирівна; Кітченко, Олена Миколаївна; Васильцова, Світлана Олександрівна (Technology audit and production reserves, 2015)
This paper discusses the development of the retail network of retail sector in Ukraine. The main aim of the study is conducting the market research of retail chains in Ukraine by the example of retailers operating in the market in order to further define the background and dynamics of the retail market of Ukraine, as well as study the role of retailers in ensuring the increase of retail sector. The basis of the study was dialectical and systematic approaches; methods of forecasting and modeling to determine the main components which may have a significant impact on the level of intensity of competition among national food chains. The results of conducted research lead to the conclusion that the most important role in the growth of retail sector in Ukraine provide retailers. It is marked that the main components that affect the level of intensity of competition are: threat of new store formats, bargaining power of suppliers, threat of entry of new competitors and the market power of buyers. The obtained results can be used by marketing managers involved in research in the field of consumer markets, as well as in decision-making in the management of marketing retailers. These experiments allow to generalize the experience of the EU countries grocery chains for control the retail market, as well as specificate the factors of influencing on buyers and tools to attract customers to the shopping center.